Multimodal approaches to Chinese-English translation and interpreting - Zhang, Meifang, 1979-; Feng, Dezheng (London ; New York : Routledge, 2021)
"Multimodal Approaches to Chinese-English Translation and Interpreting is among the first attempts to apply multimodal approaches to translation and interpreting with a special focus on Chinese-English translations and interpreting. Gathering the work of leading academics in their field, it introduces and applies different theories of the multimodal discourse analysis to the study of translations of some Chinese classics such as the Monkey King, Mulan and The Art of War, as well as of interpretations of up-to-date issues such as those related to the Chinese Bell and Road Initiative and the Macao tourism. This collection provides new understandings of transformations in the multimodal translation process and useful reference models for researchers who are interested in doing research of similar kind, especially for those who are interested in looking into translations related to Chinese language, literature and culture"--
Introduction: Multimodal Approaches to Translation and Interpreting / ZHANG Meifang and FENG Dezheng -- Intersemiotic Shifts in the Translation of Chinese Costume Drama Subtitles: A multimodal analysis approach / QIAN Hong and FENG Dezheng -- A Multimodal Study of Paratexts in Bilingual Picturebooks on Mulan / CHEN Xi -- Intersemiotic Translation of Rhetorical Figures: A case study of the multimodal translation of The Art of War / LUO Tian -- Reshaping the Heroic Image of Monkey King via Multimodality: A case study of Hero Is Back / WANG Hui and LI Xiaowei -- 'Dis'covering Hamlet in China: A case analysis of book covers of the Chinese Hamlet / XIE Guixia Rosie -- Bell and Road Initiatives in Texts and Images: A Critical Perspective on Intersemiotic Translation of Metaphors / ZHANG Xiaoyu -- A Corpus-assisted Multimodal Approach to Tourism Promotional Materials of Macao: A case study of three signature events / LAM Sut I and LEI Sao San -- Effects of Non-verbal Paratext Capturing on Meaning Transfer in Consecutive Interpreting / OUYANG Qianhua and FU Ai.
OCLC-licensed vendor bibliographic record.
Keywords: Chinese language -- Translating into English; Translating and interpreting -- China; Audio-visual translation; Semiotics; LANGUAGE ARTS & DISCIPLINES / Translating & Interpreting